Recent developments in profiled steel sheeting dry board (PSSDB) systems: A systematic literature review - Abdulrahman Mubarak Salem Sawahli; Sakhiah Abdul Kudus; Adiza Jamadin; Mohamad Farid Misnan; Kunitomo Sugiura (Results in Engineering)
The Profiled Steel Sheeting Dry Board Composite construction system consists of profiled steel sheeting with dry board, offering power-efficient, lightweight, and flexible, making it suitable for a wide range of structural applications. While there are well-founded promises from its development, there is a lack of systematic and holistic studies on its application and structure performance. This systematic literature review aims to fill this gap and report on the relevant papers to PSSDB. Using the PRISMA methodology, a systematic screening process led to the identification of 552 publications, which were then filtered down to 33 articles that all constituted relevant research papers for analysis, ensuring scientific rigour and transparency. This paper evaluates the structural performance and applications of the PSSDB system and analyses critical issues and research perspectives. Key results indicate that local buckling remains a formidable design challenge for PSS over a continuum of design cases, with few investigations proposing feasible mitigation strategies. Moreover, the dynamic behaviour of PSSDB is largely unexplored due to the limited experimental modal analysis and related investigations, where vibration performance is critical for structural integrity. It summarises existing evidence to assess current boundaries and highlights areas for future research and implications for practice. It provides a foundation to create new, effective solutions for enhancing the structural performance and the versatility of PSSDB systems. Thereby, an improved understanding of the PSSDB supports to optimise it further and widely deploying it in current construction, thus making work a novel step that fills the research gap.